Corporate Compassion: Analyzing John 15:9-17 through a Socio-Rhetorical Perspective - Salurante, Tony; Siagian, Pestaman; Wibowo, Moses (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
This research delved into the intricate facets of workplace spirituality within the contemporary context, specifically addressing labor challenges in Indonesia. The study employed socio-rhetorical analysis, anchored in John's theology from chapter 15:9-17, to explore the theological and practical dimensions of spirituality in the workplace. Selected sources from prominent databases underpinned the socio-rhetorical analysis, providing a comprehensive understanding of the subject. The findings underscored that implementing spirituality in the workplace, particularly from a Christian perspective, could foster inclusivity, harmony, and organizational efficiency. Effective communication and respect for diverse beliefs emerged as pivotal factors in ensuring universal understanding and embrace of workplace spirituality. The research contributed nuanced insights into the intersection of theology and practice, offering implications for theory and application in contemporary workplaces. It concluded that workplace spirituality, rooted in John's theology, possessed transformative potential, infusing workplaces with transcendent purpose, nurturing harmonious relationships, and cultivating effective leadership. The implications of this study extended to the broader discourse on spirituality in organizational contexts, enriching the understanding of the role of faith and theology in shaping the modern workplace, especially in the unique socio-cultural landscape of Indonesia.